Experience with gender affirming hormones and puberty blockers (gonadotropin releasing hormone agonist): a qualitative analysis of sexual function - Finegan, Jamie L; Marinkovic, Maja; Okamuro, Kyle; Newfield, Ron S; Anger, Jennifer T (Journal of sexual medicine, 2025)
Gender-affirming medical therapy (GAMT), including puberty blockers (PB) and gender-affirming hormone therapy (GAHT), is part of the transition for many transgender and nonbinary (TGNB) individuals; however, there have been few studies investigating sexual function and desire during GAMT, and no reports on individuals who received PB. We aimed to qualitatively evaluate the sexual experience of TGNB individuals during GAMT and identify significant and consistent themes that arose from our analysis. We performed an Institutional Review Board-approved two-institutional study. Our study group (n = 63) included individuals who had received or were receiving puberty blockers (GnRHa) and/or GAHT (estrogen or testosterone) at the time of enrollment. The enrolled subjects were interviewed using an open-ended topic-based guide, and qualitative analysis was performed by hand coding the interview transcripts using Constructivist Grounded Theory qualitative methods until thematic saturation was reached. A total of 63 TGNB subjects (33 transgender women, 20 transgender men, 10 non-binary, or another gender identity), aged 18-25 years, were interviewed about the effect of GAMT on their sexual function and desire. Our analysis uncovered several themes that were consistent among subjects from different subgroups. Half the participants reported feeling no regrets regarding GAMT therapy, and the other half reported that they wished they had started GAMT sooner. Two notable themes were identified: many subjects reported "less dysphoria" as a positive change in sexual desire, and others reported more enjoyable sexual experiences since being on GAMT. The subgroup of subjects with a history of GnRHa use did not differ in their experiences and responses from the subgroup on GAHT alone, which indicated no negative effect of GnRHa on sexual function. Our results illuminate the need for providers to discuss the potential impacts of GAMT on sexual function and desire with transgender and nonbinary patients. An important strength of this study is the open-ended interview design. This design allowed subjects to speak freely and openly about their experience. One limitation is a relatively small sample size, particularly of the puberty blocker (GnRHa) subgroup. A more robust sample is needed to further investigate the effect of GAMT on sexual function and desire in TGNB individuals, specifically those receiving GnRHa. Themes were similar for all subjects; however, the most prominent theme among our subjects was that the positive changes in sexual function and desire outweighed any negative changes.